Proceedings of the ACM Symposium on Applied Perception 2016
DOI: 10.1145/2931002.2963134
|View full text |Cite
|
Sign up to set email alerts
|

Psychoacoustic characterization of propagation effects in virtual environments

Abstract: As sound propagation algorithms become faster and more accurate, the question arises as to whether the additional efforts to improve fidelity actually offer perceptual benefits over existing techniques. Could environmental sound effects go the way of music, where lower-fidelity compressed versions are actually favored by listeners? Here we address this issue with two acoustic phenomena that are known to have perceptual effects on humans and that, accordingly, might be expected to heighten their experience with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Rungta et al [179] designed two experiments to analyze the psychoacoustic characterization of the sounding effects of diffraction and reverberation. They found that accurate Fig.…”
Section: Psycho-acoustic Evaluationmentioning
confidence: 99%
“…Rungta et al [179] designed two experiments to analyze the psychoacoustic characterization of the sounding effects of diffraction and reverberation. They found that accurate Fig.…”
Section: Psycho-acoustic Evaluationmentioning
confidence: 99%
“…Research on spatial audio reproduction technologies is richly varied and actively on-going -see [30] for a review, with solutions for virtual environments described, for example, in [31], and corresponding psychophysical studies reviewed in [32]. The methods employed in our experiment used state-of-the-art technology to simulate real-time three-dimensional audio spatialization and auralization [33].…”
Section: Spatial Hearingmentioning
confidence: 99%
“…In addition to specular and diffuse effects, it is also important to simulate complex diffracted scattering, occlusions, and inter-reflections that are perceptible [17,31,33]. Prior geometric methods are accurate in terms of simulating high-frequency effects and can be augmented with approximate edge diffraction methods that may work well in certain cases [41,49], though their behavior can be erratic [36]. On the other hand, wave-based precomputation methods can accurately simulate these effects, but are limited to static scenes [33,34].…”
Section: Introductionmentioning
confidence: 99%